Penerapan Produk Blue Economy Melalui Pembuatan Nugget Udang Di Kampung Matara Merauke Papua Selatan - Prima Lestari Situmorang; Riris Lawitta Maulina Siahaan; Najdah Thalib; Juli Arianti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
and sustainability of natural potential so that marine resources are maintained and can be used by the next generation. Matara Village is a coastal area in Merauke, south papua South Papua Province which has abundant marine potential. One of them is shrimp which is a leading commodity in this village. The use of shrimp is still limited to selling them whole. In the process, the shrimp are sold at cheap prices to agents and often the small shrimp are not sold so they are wasted which ultimately causes an unpleasant smell on the beach. Apart from that, fishermen in Matara Village generally live in the lower middle economic strata. The abundance of marine products has not been processed optimally. In fact, if the Blue Economy is implemented optimally, it can increase the income of the people there. Training and assistance in making Blue Economy products in the form of shrimp nuggets was provided to the women of Matara Village. as an effort to increase the economic value of shrimp, increase the variety of healthy foods that are contemporary and popular with all groups, overcome waste caused by unsold small shrimp, and can increase income variations This activity was carried out by Musamus University KKN lecturers and students for 1 month. This activity was carried out by observing the community, lectures about the importance of implementing the Blue Economy concept in coastal areas, demonstrations and assistance in making shrimp nuggets, and surveying community satisfaction. This activity was responded very well by the community and said that assistance should be carried out in the manufacture of Blue Economy products in the future